The state of missiology today : global innovations in Christian witness - Engen, Charles Edward van (Missiological engagements, 2016)
Mission is constantly innovating. As contexts change, so too does the work of the church. Today, in the face of a rapidly changing world and a growing global church, the task of mission must continue to innovate in unexpected ways. The State of Missiology Today explores the developments and transformations in the study and practice of mission. Looking both backwards--especially over the first half-century of Fuller Theological Seminary's School of Intercultural Studies--and forwards, the contributors to this volume chart the current shape of mission studies and its prospects in the twenty-first century.